Analisis CAMEL untuk Menilai Tingkat Kesehatan Laporan Keuangan Pada PT Bank MNC Internasional Tbk - Ari Susantiaji; Suci Indah Nova Aulia; Ardina Wuri Hermayanti (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2022)
In the 4.0 era, the financial industry is one of the important roles to advance a country's economy and is needed in financial transaction activities in all sectors. The main function of banking is to effectively increase the added value of the economy. The effectiveness of a bank can be seen in the assessment of the level of bank health which can be viewed from several indicators, one of which is through an assessment in the financial statements of the bank concerned using the CAMEL method. The purpose of this study is to determine the level of health in the financial statements of PT Bank MNC Internasional Tbk in the 2018-2021 period using the CAMEL method which includes factors from Capital, Asset, Management, Earning and Liquidity. The design of this study used descriptive analysis using a content or document analysis. The results of the analysis showed that PT Bank MNC Internasional Tbk showed its achievements in the ratio of CAR, BOPO and LDR. However, based on the results of the bank's health level analysis using the CAMEL analysis for the 2018-2021 period, it was generally declared unhealthy.